Just War Theory: An analysis of its relevance for contemporary warfare and states - Gray, Susan L (University of Ottawa (Canada), 2009)
Contemporary Just War Theory (JWT) is the philosophical theory used to determine the moral and ethical issues surrounding warfare and it is currently at a crossroads. Most applications of JWT (within the last century) presuppose at least the following: the conflict's participants are traditionally defined and known states; the world structure is state-based; most conflicts are divisible into stages (in simple terms: pre-conflict, conflict and post-conflict); and, finally, a clear outcome will mean victory for one side, be it one state or an allied group of states. In light of Philip Bobbitt's non-traditional global market state model, is conventional JWT still valid for determining the ethical scope of the types of conflicts emerging in the 21st century? This study explores some of these recent calls for the adaptation and revision of JWT and applies contemporary JWT to a phenomenon of the global market state: the rise of the private military industry. Based on this application, I found that JWT could not assess Private Military Contractor (PMC) activity on three counts. As PMCs operation within the limits of privacy, JWT cannot assess their actions and the behaviour and judgment of their members as JWT's ad bellum and in bello principles are designed to apply to public actors: namely legitimate states, their political leaders and militaries. Secondly, due to the private nature of PMC contracts and terms of service, the principle of proportionality cannot be applied to their activity. Finally, PMCs obscure the principles of proper authority and public declaration; a state that may not have the public support of its nation to actively influence a war or engage in it altogether can seek to a void any open declaration of war and employ a PMC instead of its own military. With regard to modern JWT itself, I concluded that three areas need revision: the decreasing difference between pre-emptive war and preventive strikes; the jus in bello issue of discrimination between legitimate and non-legitimate targets; and the responsibilities and principles that should govern the moral behaviour involved in restoring the pre-conflict status quo deserve substantial study.
Keywords: Philosophy.; Political Science, General.